Stimuli that induce a cholinergic neuronal phenotype of NG108-15 cells upregulate ChAT and VAChT mRNAs but fail to increase VAChT protein - Dolezal, V; Castell, X; Tomasi, M; Diebler, M F (Brain research bulletin, 2001)
The vesicular acetylcholine transporter (VAChT) and choline acetyltransferase (ChAT) are encoded by genes organized in a single gene locus, and coregulation of the transcription of the two genes has been repeatedly reported in cholinergic tissues. In the present study, different stimuli were used to induce the differentiation of the hybridoma cells NG108-15 and we examined their effects on the modulation of VAChT and ChAT expression at the mRNA and protein levels. All agents upregulated the VAChT and ChAT mRNA levels, but to a different extent. ChAT activity was increased by retinoic acid, dexamethasone, and dibutyrylcyclic AMP (dbcAMP), and a synergistic effect was observed with a combined dexamethasone and dbcAMP treatment. Nonetheless, no changes in the VAChT protein level could be observed, as judged from ligand binding studies as well as from immunochemical detection. Hemicholinium-3-sensitive choline uptake, hemicholinium-3 binding, and acetylcholine content were increased by differentiating agents, with a rank order of potency comparable to their effects on ChAT activity. Prominent changes were observed in the expression of vesicular protein markers, particularly with the associated treatment dexamethasone and dbcAMP. Thus, it appears that although the different stimuli we have been using are able to stimulate neuronal features and activate the transcription of cholinergic genes, they did not contrive to increase the level of VAChT protein in these cells.
Keywords: vezikulární transportní proteiny acetylcholinu; cholin-O-acetyltransferasa; vezikulární transportní proteiny; antiflogistika; transportní proteiny; Hybridomas; dibutyryl cyklický AMP; Phenotype; buněčné linie; Vesicular Transport Proteins; cholin; Tretinoin; Choline; Membrane Transport Proteins; tretinoin; keratolytika; acetylcholin; Transcription, Genetic; membránové transportní proteiny; messenger RNA; proteiny nervové tkáně; Cell Line; RNA, Messenger; Vesicular Acetylcholine Transport Proteins; Carrier Proteins; genetická transkripce; Keratolytic Agents; Nerve Tissue Proteins; Acetylcholine; dexamethason; Anti-Inflammatory Agents; Choline O-Acetyltransferase; Dexamethasone; Bucladesine; fenotyp; hybridomy